Research on the Plateau languages of Central Nigeria (Afrika und Übersee, 2020)
The paper is an overview of scholarship on the Plateau language group of Central Nigeria to November 2020. It reviews the existing published and manuscript sources and describes modern scholarship. It provides an overview of the literature on the internal and external classification of these languages and the issue of endangerment, which is severe for some languages. It summarises the use of Plateau languages in education and the media, which has undergone a major revival after 2010. There is now a concerted push for the use of Plateau languages in education. The paper then reviews each subgroup, presenting an internal classification and references to publications. Based on the existing evidence, a fresh classification of Plateau is presented.
Keywords: Plateau languages; classification; media; Nigeria